719 REDUCED MEAN NOCTURNAL BASELINE IMPEDANCE AIDS DIAGNOSIS OF GASTRO-ESOPHAGEAL REFLUX DISEASE AND LARYNGOPHARYNGEAL REFLUX DISEASE. (17th September 2021) - Park, Jin-soo; Van der Wall, Hans; Falk, Gregory
Abstract:  : Laryngopharyngeal reflux disease (LPR) and gastro-esophageal reflux disease (GERD) occur due to acidic gastric refluxate causing symptoms. Baseline esophageal impedance has been shown to be reduced with prolonged acid exposure. Mean nocturnal baseline impedance (MNBI) is a novel measure that has shown promise in GERD but has not been evaluated in LPR. This study aimed to assess the role of MNBI in LPR and GERD patients. Methods: Off-therapy impedance-pH tracings were blindly reviewed for 187 patients previously prospectively allocated clinical diagnoses of LPR (n = 105) or GERD (n = 82). Conventional impedance-pH measures and MNBI were analysed for the two groups. Results: MNBI was significantly lower in the distal esophagus in GERD patients compared with LPR (1679 ± 914 vs. 2109 ± 863; p = 0.001). Similarly, in the proximal esophagus, MNBI was lower in GERD than LPR (2289 ± 579 vs. 2541 ± 471; p = 0.001). In the pharynx, MNBI was similar between the two groups (2116 ± 699 vs. 2133 ± 770; p = 0.878). Distal acid exposure time (AET) and the number of distal acid reflux episodes negatively correlated with distal esophageal MNBI (r = −0.195; p = 0.007) and (r = −0.330; p < 0.001) respectively. Conclusion: Baseline impedance was reduced in both LPR and GERD at both distal and proximal esophageal measurements, and more severely reduced in GERD. Baseline impedance is strongly and inversely related to acid exposure in the esophagus. Pharyngeal MNBI was not reduced or different between groups. Distal and proximal esophageal MNBI may be useful in diagnosis of LPR as well as GERD.